Polyhydroxyalkanoates production by photosynthetic mixed cultures - Fradinho, Joana Costa (2013)
Polyhydroxyalkanoates (PHAs) are natural biologically synthesized polymers that have been the subject of much interest in the last decades due to their biodegradability. Thus far, its microbial production is associated with high operational costs, which increases PHA prices and limits its marketability. To address this situation, this thesis’ work proposes the utilization of photosynthetic mixed cultures (PMC) as a new PHA production system that may lead to a reduction in operational costs. In fact, the operational strategies developed in this work led to the selection of PHA accumulating PMCs that, unlike the traditional mixed microbial cultures, do not require aeration, thus permitting savings in this significant operational cost. In particular, the first PHA accumulating PMC tested in this work was selected under non-aerated illuminated conditions in a feast and famine regime, being obtained a consortium of bacteria and algae, where photosynthetic bacteria accumulated PHA during the feast phase and consumed it for growth during the famine phase, using the oxygen produced by algae. In this symbiotic system, a maximum PHA content of 20% cell dry weight (cdw) was reached, proving for the first time, the capacity of a PMC to accumulate PHA. During adaptation to dark/light alternating conditions, the culture decreased its algae content but maintained its viability, achieving a PHA content of 30% cdw. Also, the PMC was found to be able to utilize different volatile fatty acids for PHA production, accumulating up to 20% cdw of a PHA co-polymer composed of 3-hydroxybutyrate (3HB) and 3-hydroxyvalerate (HV) monomers. Finally, a new selective approach for the enrichment of PMCs in PHA accumulating bacteria was tested. Instead of imposing a feast and famine regime, a permanent feast regime was used, thus selecting a PMC that was capable of simultaneously growing and accumulating PHA, being attained a maximum PHA content of 60% cdw, the highest value reported for a PMC thus far. The results presented in this thesis prospect the utilization of cheap, VFA-rich fermented wastes as substrates for PHA production, which combined with this new photosynthetic technology opens up the possibility for direct sunlight illumination, leading to a more cost-effective and environmentally sustainable PHA production process.